Beyond Substrates: Strain Engineering of Ferroelectric Membranes. Issue 43 (22nd September 2020) - Pesquera, David; Parsonnet, Eric; Qualls, Alexander; Xu, Ruijuan; Gubser, Andrew J.; Kim, Jieun; Jiang, Yizhe; Velarde, Gabriel; Huang, Yen‐Lin; Hwang, Harold Y.; Ramesh, Ramamoorthy; Martin, Lane W.
Abstract: Strain engineering in perovskite oxides provides for dramatic control over material structure, phase, and properties, but is restricted by the discrete strain states produced by available high‐quality substrates. Here, using the ferroelectric BaTiO3, production of precisely strain‐engineered, substrate‐released nanoscale membranes is demonstrated via an epitaxial lift‐off process that allows the high crystalline quality of films grown on substrates to be replicated. In turn, fine structural tuning is achieved using interlayer stress in symmetric trilayer oxide‐metal/ferroelectric/oxide‐metal structures fabricated from the released membranes. In devices integrated on silicon, the interlayer stress provides deterministic control of ordering temperature (from 75 to 425 °C) and releasing the substrate clamping is shown to dramatically impact ferroelectric switching and domain dynamics (including reducing coercive fields to <10 kV cm −1 and improving switching times to <5 ns for a 20 µm diameter capacitor in a 100‐nm‐thick film). In devices integrated on flexible polymers, enhanced room‐temperature dielectric permittivity with large mechanical tunability (a 90% change upon ±0.1% strain application) is demonstrated. This approach paves the way toward the fabrication of ultrafast CMOS‐compatible ferroelectric memories and ultrasensitive flexible nanosensor devices, and it may also be leveraged for the stabilization of novel phases and functionalities not achievable via direct epitaxial growth. Abstract : Upon release from their growth substrates, the properties of single‐crystal ferroelectric BaTiO3 membranes integrated on silicon are tuned via the interlayer stress from epitaxially coupled electrode layers where the removal of substrate clamping improves the polarization switching speed. Using this strategy, highly sensitive mechanical control of the dielectric properties in membranes integrated on polymers is also demonstrated.